Preparation a Composite Material (UP/Cann F) with Evaluation Its Toughness Under the Influence of Temperature and Humidity. - A.M. Habib, Nasser (Anbar Journal of Engineering Sciences, 2012)
In this research we have prepared a composite material by using Vegetative Cellulose Fibers of Cannabis (Cann F) to reinforced a matrix of Unsaturated Polyester (UP) resin. This kind of fibers is distinguished by good properties such as high tensile strength, low elongation, thermal resistance and low cost. The impact strength was tested by using Charpy method for three materials (UP resin), composite (UP / Cann F) and composite (UP/Glass F). The results indicated that the fracture energy (Uc) decreased as the notch depth (a) increased on the sample from (0.7 mm) up to (4.9 mm). However, the fracture energy increased as the temperature of the composite increased for different temperatures of (0, 35, 50 and 75) oC. It was noticed that the Material toughness (Gc) has been improved significantly, where in case of the composite (UP /Cann F), the improvement of (Gc) was from (2.45 kJ/m2 ) to (14.5 kJ/m2 ) and it was (17 kJ/m2 ) for composite (UP/GF) has been measured at (35) oC. When those composite materials (UP/Cann F) exposed to humidity for a period of (72 hrs) without immersion, their properties did not change, hence the effects are not of chemical but of physical nature. The conclusion, the difference between the toughness of the material (Gc) for the reinforced composites by Cannabis and E-glass fibers for all temperatures is not large, so this encourage the development of Cannabis fiber reinforced composites in the future to abundance, and low cost for industrial investment